Performance Analysis of Water Injection Well BEL-13 and Production Well BEL-01 Using Hall Plot and Buckley-Leverett Methods - Yanni Florensia Imanuela Sairlela; Muhammad Taufiq Fathaddin; Ridha Husla (Penerbitan Universitas Trisakti, 2023)
At first, the FLO field had an ability to flow fluids to the surface in a natural flow, but the production capacity decreased with time. Therefore, production is increased using the waterflooding method. The purpose of this study was to analyze the performance of waterflooding carried out on injection well BEL-13 and production well BEL-01. There are two methods used in this study to achieve the desired aims and objectives, namely the Hall Plot method and the Buckley-Leverett method. The Hall Plot method was used to see the connectivity conditions between injection and production wells after being injected with water periodically. Whereas the Buckley-Leverett method was used to estimate the time of water breakthrough, production amount (Np), the injection rate (Wi), water cut value (WC), and recovery factor (RF). Based on the Hall Plot method, it was found that the waterflooding carried out was stable or normal because there was no negative skin or positive skin. In addition, based on relative permeability curve, rock wettability of the reservoir rock is water wet. Analysis using Buckley-Leverett shows that the cumulative production at the time of water breakthrough from the injection well BEL-13 to the production well BEL-01 is 364,733.64 STB. When the water breakthrough occurs, the predictions of WOR, water cut, and recovery factor are 2.13, 68.08%, and 29.76%.